2011
DOI: 10.1021/jp204283k
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sol–Gel-Formed ZnO:Al Processing Parameters by Observation of Dopant Ion Location Using Solid-State 27Al NMR Spectrometry

Abstract: Studies on the properties of zinc oxide (ZnO) have been well-reviewed, 1À3 with many applications proposed such as thin-film solar cells 1 and optoelectronic materials. 3 The performance of doped ZnO as a transparent conducting oxide (TCO) prepared using techniques such as magnetron sputtering, chemical vapor deposition, and pulsed laser deposition has provided a solid body of knowledge. 1 Zn is cheap and abundant, making doped ZnO a favored candidate to replace TCOs based on indium tin oxide (ITO) for thin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 36 publications
6
38
0
Order By: Relevance
“…However we have to note, that the integration of solid-state 27 Al-NMR spectra signals does not provide reliable quantitative data. For all probes we identified amounts smaller 0.2 at.% for Al4 sub that is in accordance with the findings of Avadhut et al [25] and other authors who identified just small amounts of in ZnO solubilized aluminum by 27 Al-NMR [24,28,32]. With increasing hydration ratio the amount of crystalline located aluminum decreases from 0.15 at.% to 0.05 at.% Al and the amount for amorphous located aluminum increases from 1.85 at.% up to 1.95 at.% Al.…”
Section: Incorporation Of Aluminum In Zno and Electrical Properties Osupporting
confidence: 92%
See 1 more Smart Citation
“…However we have to note, that the integration of solid-state 27 Al-NMR spectra signals does not provide reliable quantitative data. For all probes we identified amounts smaller 0.2 at.% for Al4 sub that is in accordance with the findings of Avadhut et al [25] and other authors who identified just small amounts of in ZnO solubilized aluminum by 27 Al-NMR [24,28,32]. With increasing hydration ratio the amount of crystalline located aluminum decreases from 0.15 at.% to 0.05 at.% Al and the amount for amorphous located aluminum increases from 1.85 at.% up to 1.95 at.% Al.…”
Section: Incorporation Of Aluminum In Zno and Electrical Properties Osupporting
confidence: 92%
“…Independent from the hydration ratio the initially inserted aluminum concentration of 2 at.% could be found within the limits of the standard deviation (Table 1). Al-nuclear magnetic resonance spectroscopy ( 27 Al-NMR) the distribution of the aluminum atoms in the host lattice of ZnO can be depicted and characterized [23,24,25,26,27,28]. Related to the crystallographic composition of the wurtzite-structured zinc oxide, different lattice sites can be occupied by the dopant.…”
Section: Incorporation Of Aluminum In Zno and Electrical Properties Omentioning
confidence: 99%
“…In comparison with other findings, 23,25 Fig . 8 presents the high-resolution O 1s spectrum acquired on 0.5 at% ZnO:Al spherical nanocrystals.…”
Section: Resultsmentioning
confidence: 51%
“…27 The octahedral coordination, where the Al 3+ ion behaves as an acceptor, would decrease conductivity. 23,25,28 Thus, the Al 3+ dopant should be placed in a substitutional, tetrahedral position to effectively modify the electronic properties of the ZnO host material. Even though the Al 3+ ion is smaller than the Zn 2+ ion, it has a preference for the octahedral site in most Al-containing oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid phase preparation of transparent conductive AZO nanocrystals is dominated by sol-gel techniques. [8][9][10][11][12] A number of studies have examined the influence of solvent, temperature, 13 crystallinity, 14 doping concentration 13,[15][16][17][18] and heating profile 18 on film properties, which slightly differ with respect to the resistivity and optical transparency. Despite the complexity of the material there is a consensus that an optimum doping level exists, which however is difficult to compare because the authors often only refer to the Al to Zn ratio in the start mixture.…”
Section: Introductionmentioning
confidence: 99%